7 Tesla (T) human cardiovascular magnetic resonance imaging using FLASH and SSFP to assess cardiac function: validation against 1.5 T and 3 T. - Suttie, J; Delabarre, L; Pitcher, A; van de Moortele, P; Dass, S; Snyder, C; Francis, J; Metzger, G; Weale, P; Ugurbil, K; Neubauer, S; Robson, M; et al. (2012)
We report the first comparison of cardiovascular magnetic resonance imaging (CMR) at 1.5 T, 3 T and 7 T field strengths using steady state free precession (SSFP) and fast low angle shot (FLASH) cine sequences. Cardiac volumes and mass measurements were assessed for feasibility, reproducibility and validity at each given field strength using FLASH and SSFP sequences. Ten healthy volunteers underwent retrospectively electrocardiogram (ECG) gated CMR at 1.5 T, 3 T and 7 T using FLASH and SSFP sequences. B1 and B0 shimming and frequency scouts were used to optimise image quality. Cardiac volume and mass measurements were not significantly affected by field strength when using the same imaging sequence (P > 0.05 for all parameters at 1.5 T, 3 T and 7 T). SSFP imaging returned larger end diastolic and end systolic volumes and smaller left ventricular masses than FLASH imaging at 7 T, and at the lower field strengths (P < 0.05 for each parameter). However, univariate general linear model analysis with fixed effects for sequence and field strengths found an interaction between imaging sequence and field strength (P = 0.03), with a smaller difference in volumes and mass measurements between SSFP and FLASH imaging at 7 T than 1.5 T and 3 T. SSFP and FLASH cine imaging at 7 T is technically feasible and provides valid assessment of cardiac volumes and mass compared with CMR imaging at 1.5 T and 3 T field strengths.